Examining the Employment Dimension of Corporate Social Responsibility (Between Global Initiatives and Indonesia Statutory) - Santoso, Budi; .Hussein, Safinaz Mohd; Prasasti, Dina Mila; Lestari, Sinta; Syamsudin, Ummu Sulaem (Faculty of Law, Universitas Sebelas Maret, 2023)
This article examines the employment aspects of CSR regulations. Every company needs a reference to verify its CSR activities support economic, social, and environmental development. The government has enacted laws to encourage corporate social responsibility (CSR). Since CSR funds are in the company's income statement, they often conflict with fiduciary duty. The study reveals that business views on CSR's employment dimension have shifted. Initially, CSR managed risk and prevented reputational and financial damages. Labor was considered an expense, not an investment. Many companies now employ CSR as a key value and competitive advantage